Rating behavioral problems in adolescent eating disorders: Parent-child differences. (April 2021) - Mensi, Martina M.; Rogantini, Chiara; Provenzi, Livio; Borgatti, Renato
Highlights: Behavioral problems are frequent among adolescents with eating disorders. In this sample, patients self-reported scores were lower in somatic complaints, thought problems and rule-breaking compared to their parents ratings. These discrepancies were influenced by patients' clinical and psychosocial features. A multi-informant behavioral problems assessment is needed in psychiatric settings. Abstract: The primary objective of this study was to investigate the discrepancies among the perception of behavioral problems self-reported by adolescent patients with restrictive eating disorders (REDs) and rated by their mothers and fathers. Forty-eight female adolescents with RED filled in the Youth Self-Report, their mothers and fathers separately completed the Child Behavior Check List. Patients reported lower scores for somatic complaints, thought problems, and rule-breaking behaviors compared to their mothers and fathers. These findings may inform clinical consultation and treatment.